JUSTICE IN PARTNED IN THE LEGAL SYSTEM OF PANCASILA AS THE PARENT OF STRENGTHENING THE VALUE OF UNITY AND UNITY - Nunung Nugroho (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2021)
Pancasila as the source of all sources of law in Indonesia. Especially is the side of the value of justice itself which reflects on justice with dignity as a characteristic of justice for the Indonesian nation. The theory of justice which is based on the values of Pancasila, especially the second principle, namely the principle of humanity that is just and civilized and is supported by the first principle of God Almighty. The terms fair and civilized as meant in the second principle of Pancasila, are interpreted by Notonagoro as a sense of humanity that is fair to oneself, to fellow humans, and toGod (causa prima). Based on this fair and civilized humanitarian principle, legal justice that is owned by the Indonesian nation is justice that humanizes humans. According to Teguh Prasetyo, justice that humanizes humans is called a dignified theory of justice. In the sense that even though someone has been legally guilty, that person must still be treated as a human being in accordance with their inherentrights. So that justice with dignity is justice that balances rights and obligations. The value of unity and integrity is based on and imbued with the first sila (divinity), the second principle (just and civilized humanity) and underlies and animates the fourth principle (democracy led by wisdom in deliberation / representation) and the fifth principle (social justice for all Indonesian people). Thus, the value of unity and integrity in question is unity and unity that is godly, humane, human, and just, which are the characteristics of the Pancasila legal system.